Impact of intravenous vitamin C as a monotherapy on mortality risk in critically ill patients: A meta-analysis of randomized controlled trials with trial sequential analysis - Hung, Kuo-Chuan; Chuang, Min-Hsiang; Chen, Jen-Yin; Hsu, Chih-Wei; Chiu, Chong-Chi; Chang, Ying-Jen; Lee, Chia-Wei; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Nutrition, 2023)
Background: This meta-analysis aimed at investigating the pooled evidence regarding the effects of intravenous vitamin C (IVVC) on mortality rate in critically ill patients. Methods: Databases including Medline, Embase, and Cochrane Library were searched from inception to October, 2022 to identify RCTs. The primary outcome was the risk of overall mortality. Subgroup analyses were performed based on IVVC dosage (i.e., cut-off value:100mg/kg/day or 10000mg/day). Trial sequential analysis (TSA) was used to examine the robustness of evidence. Results: A total of 12 trials including 1712 patients were analyzed. Although meta-analysis demonstrated a lower risk of mortality in patients with IVVC treatment compared to those without [risk ratio(RR): 0.76, 95%CI: 0.6 to 0.97, p=0.02, I2=36%, 1711 patients), TSA suggested the need for more studies for verification. Moreover, subgroup analyses revealed a reduced mortality risk associated with a low IVVC dosage (RR=0.72, p=0.03, 546 patients), while no beneficial effect was noted with high IVVC dosage (RR=0.74, p=0.13, I2=60%, 1165 patients). The durations of vasopressor [mean difference (MD): -37.75 hours, 404 patients) and mechanical ventilation (MD: -47.29 hours, 388 patients) use were shorter in the IVVC group than those in the controls, while there was no significant difference in other prognostic outcomes (e.g., length of stay in intensive care unit/hospital) between the two groups. Conclusion: Although intravenous vitamin C as a monotherapy reduced pooled mortality, durations of vasopressor use and mechanical ventilation, further research is required to support our findings and to identify the optimal dosage of vitamin C in the critical care setting.